35. CURRENT STATUS OF REASONABLE USE OF ANTIBIOTICS AT HOSPITAL 199 IN 2023 - 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Analyzing the situation of rational antibiotic usage at Hospital 199 in 2023–2024. Research method: cross-sectional study, secondary data analysis (retrospective), survey of 300 medical records with antibiotic use, inpatient treatment for 3 days or more for the following diseases: respiratory infections, urinary tract infections, skin and soft tissue infections, and abdominal cavity infections. The study was conducted from January 2023 to September 2023. Results: The proportion of rational antibiotic use was 65.7%. The propottion of appropriate first-time antibiotic use was 74%. Age, treatment department, treatment date, and treatment efficacy were associated with appropriate antibiotic use.
Keywords: Antibiotic usage; antibiotic resistance; Hospital 199